Elamipretide (SS-31) Improves Functional Connectivity in Hippocampus and Other Related Regions Following Prolonged Neuroinflammation Induced by Lipopolysaccharide in Aged Rats - Liu, Yang; Fu, Huiqun; Wu, Yan; Nie, Binbin; Liu, Fangyan; Wang, Tianlong; Xiao, Wei; Yang, Shuyi; Kan, Minhui; Fan, Long (Frontiers in Aging Neuroscience, 2021)
Neuroinflammation has been recognized as a major cause for neurocognitive diseases. Although the hippocampus has been considered an important region for cognitive dysfunction, the influence of hippocampal neuroinflammation on brain functional connectivity (FC) has been rarely studied. In this study, lipopolysaccharide (LPS) was used to induce systemic inflammation and neuroinflammation in the aged rat brain, while elamipretide (SS-31) was used for treatment. Systemic and hippocampal inflammation were determined using ELISA, while astrocyte responses during hippocampal neuroinflammation were determined by interleukin 1 beta (IL-1β)/tumor necrosis factor alpha (TNFα) double staining immunofluorescence. Oxidative stress was determined by reactive oxidative species (ROS), electron transport chain (ETC) complex, and superoxide dismutase (SOD). Short- (<7 days) and long-term (>30 days) learning and spatial working memory were tested by the Morris water maze (MWM). Resting-state functional magnetic resonance imaging (rs-fMRI) was used to analyze the brain FC by placing seed voxels on the left and right hippocampus. Compared with the vehicle group, rats with the LPS exposure showed an impaired MWM performance, higher oxidative stress, higher levels of inflammatory cytokines, and astrocyte activation in the hippocampus. The neuroimaging examination showed decreased FC on the right orbital cortex, right olfactory bulb, and left hippocampus on day 3, 7, and 31, respectively, after treatment. In contrast, rats with SS-31 treatment showed lower levels of inflammatory cytokines, less astrocyte activation in the hippocampus, and improved MWM performance. Neuroimaging examination showed increased FC on the left-parietal association cortex (L-PAC), left sensory cortex, and left motor cortex on day 7 with the right flocculonodular lobe on day 31 as compared with those without SS-31 treatment. Our study demonstrated that inhibiting neuroinflammation in the hippocampus not only reduces inflammatory responses in the hippocampus but also improves the brain FC in regions related to the hippocampus. Furthermore, early anti-inflammatory treatment with SS-31 has a long-lasting effect on reducing the impact of LPS-induced neuroinflammation.